PERBANDINGAN DISCOVERY LEARNING DENGAN PROBLEM BASED LEARNING BERBANTUAN LKPD PADA KURIKULUM MERDEKA MATERI BENTUK ALJABAR SEKOLAH MENENGAH - Sari, Eviana; Dewi Risalah; Utin Desy Susiaty (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to find out the comparison of the Discovery Learning model with Problem Based Learning on the learning outcomes assisted by LKPD in the Merdeka Curriculum with Algebra Form Material. This research was carried out on September 24 2024 at SMP Negeri 1 Sungai Kakap. This design involved 2 classes studied, namely the Discovery Learning learning model applied in the experimental class, namely class VII E, and the Problem Based Learning learning model applied in the control class, namely class VII C. The population in this study was class VII of SMP Negeri 1 Sungai Kakap in the academic year. 2023/2024, totaling 182 students. In this research, the method used was a quantitative experimental method, with a quasi-experimental research design, post test only control group design. Based on the research conducted, the average score for the experimental class was 73.97 and the control class was 70.58. Based on calculations that Z_count=-0.0034 and Z_table=1.96. Because Z_count< Z_table, namely -0.0034<1.69, then H_0 is accepted, which means H_1 is rejected. So it can be concluded that there is no difference in student learning outcomes taught using the Discovery Learning learning model and the Problem Based Learning learning model in algebra form material in class VII SMP Negeri 1 Sungai Kakap.